2022
DOI: 10.3389/fnetp.2022.868092
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Understanding Aberrant Brain Networks in Epilepsy

Abstract: Epilepsy is a neurological disorder affecting approximately 70 million people worldwide. It is characterized by seizures that are complex aberrant dynamical events typically treated with drugs and surgery. Unfortunately, not all patients become seizure-free, and there is an opportunity for novel approaches to treat epilepsy using a network view of the brain. The traditional seizure focus theory presumed that seizures originated within a discrete cortical area with subsequent recruitment of adjacent cortices wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Multiple studies have reported changes that discriminate between the inter‐ictal and pre‐ictal state at various scales of neuronal organization from the local to the network level. This further provides evidence that epilepsy is a large‐scale brain network disease that requires novel approaches to improve understanding of the network's aberrant structure and function 9 . New approaches with minimally invasive and non‐invasive devices providing multimodal predictive biomarkers and conducted over prolonged periods are of interest for broader application.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Multiple studies have reported changes that discriminate between the inter‐ictal and pre‐ictal state at various scales of neuronal organization from the local to the network level. This further provides evidence that epilepsy is a large‐scale brain network disease that requires novel approaches to improve understanding of the network's aberrant structure and function 9 . New approaches with minimally invasive and non‐invasive devices providing multimodal predictive biomarkers and conducted over prolonged periods are of interest for broader application.…”
Section: Introductionmentioning
confidence: 95%
“…Considering the brain as a complex network, with its structure and dynamics evolving in time, 43,44 has led to a paradigm shift in establishing epilepsy as a large-scale network disorder. 9,[45][46][47] Graph-theoretical concepts and methods 27 then enable improved characterizations of such networks. Early network-based seizure-prediction studies [48][49][50][51] have reported limited predictive performance from temporal changes of global network characteristics that assess the network's functional segregation, integration, or robustness.…”
Section: Seizure Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy has been identified increasingly as a network disorder, [11][12][13] and non-invasive imaging modalities, such as resting-state functional magnetic resonance imaging (rs-fMRI), have revealed both focal and global functional epileptic network abnormalities. [14][15][16] These network abnormalities can be used as biomarkers, helping to guide therapeutic decision-making non-invasively.…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy has been increasingly identified as a network disorder [11][12][13] . The study of brain connectomics has demonstrated the presence of large-scale network abnormalities even in focal epilepsies [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%